Finite element simulation on composite materials - Lau, Wei Peng. (2011)
In the present study, the author uses finite element method to simulate hypothetical bi-continuous composite in a bid to find out if there is potential for further study and development. The aim of the study is to investigate if the domain size of the constituent phase, will affect the effective elastic properties of the composite when the two constituent phases have a ratio difference of 20 or more between their Young’s modulus.